Counting every mother: Strengthening maternal mortality data in Nepal- A narrative review article - Acharya, Shijan; Shrestha, Bidhya; Khatiwada, Padma Prasad (Journal of Gandaki Medical College-Nepal, 2025)
Introduction: Maternal mortality remains a major public health concern in Nepal, and accurate measurement is vital for evidence-based policymaking and achieving Sustainable Development Goal 3.1, which targets a reduction in maternal deaths. This study reviews methodologies used to measure maternal mortality and evaluates the quality of related data across four dimensions- completeness, accuracy, timeliness, and consistency.Methods: A narrative review was conducted using national data sources such as the National Population and Housing Census, Demographic and Health Surveys, and Maternal Mortality and Morbidity Studies. Relevant WHO and UN guidelines were reviewed to assess the extent to which Nepal’s methodologies align with global standards.Results: The Demographic and Health Surveys provides standardized maternal death information but is limited by small sample sizes, recall bias, and the absence of cause-of-death data. The national census offers comprehensive coverage and regional disaggregation, yet data accuracy is affected by cultural barriers, underreporting, and reliance on household reporting. While Demographic and Health Surveys ensures methodological consistency across survey rounds, the decennial census restricts trend analysis due to infrequent data collection. Demographic and Health Surveys produces relatively timely data, but the census suffers from delayed reporting and limited inclusion of mobile populations. Overall, both data sources contribute valuable insights but demonstrate gaps in completeness, accuracy, and timeliness.Conclusions: Strengthening Nepal’s maternal mortality data requires adopting WHO-recommended standards, integrating International Classification of Disease- Maternal Mortality classifications, enhancing statistical validation, and leveraging digital data systems. Reliable, timely, and consistent data are essential for effective maternal health planning and achieving national and global maternal mortality targets.